Features of right lobe liver transplantation from living related donor - O. H. Kotenko; A. A. Minich (Zaporožskij Medicinskij Žurnal)
Aim. To determine the peculiarities of liver transplantation using right lobe graft from living related donor with and without the middle hepatic vein inclusion.